2001
DOI: 10.1176/appi.ajp.158.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Dysfunction in Depressed Suicide Attempters

Abstract: Neuropsychological deficits in depressed patients with high-lethality prior suicide attempts suggest impairment of executive functioning beyond that typically found in major depression. This more extensive neuropsychological impairment in the context of depression may be a risk factor for severe suicide attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
276
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(303 citation statements)
references
References 59 publications
20
276
2
5
Order By: Relevance
“…It is difficult to say to what extent our results affect the interpretation of earlier findings of association of suicide attempt history with executive impairment in younger individuals (10, 15, 35), not only because of the difference in age, but also because different tests were used. A conservative conclusion would be that the stage of the suicidal process where executive deficits may play a role is yet to be established.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It is difficult to say to what extent our results affect the interpretation of earlier findings of association of suicide attempt history with executive impairment in younger individuals (10, 15, 35), not only because of the difference in age, but also because different tests were used. A conservative conclusion would be that the stage of the suicidal process where executive deficits may play a role is yet to be established.…”
Section: Discussionmentioning
confidence: 57%
“…In the first comprehensive study of cognitive performance in attempted suicide, Keilp and colleagues (10) found evidence of executive deficits in high-lethality suicide attempters, specifically on tasks requiring organization and focused effort: the Stroop interference task, the A not B task, verbal fluency task, and the Wisconsin Card Sorting Task (WCST), where suicide attempters failed to maintain cognitive set (10). Subsequent studies have found impairment in specific aspects of executive function, including attentional control (11, 15), response inhibition (14), and verbal fluency (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests of neuropsychological functioning in depressed suicidal attempters in controls have implicated abnormalities in executive function (Keilp et al 2001), including in older adults (King et al 2000). Rubio and colleagues reported significantly greater hippocampal neurofibrillary pathology in postmortem analysis of elderly suicides and controls (Rubio et al 2001).…”
Section: Neurobiological Factorsmentioning
confidence: 99%
“…For example, Keilp and colleagues 16 found that depressed, high-lethality suicide attempters performed worse than nonpatients on several neuropsychological measures, and also performed significantly worse than low-lethality attempters on tests of executive functioning. A follow-up study concluded that impaired attention was related to suicidal behavior beyond what could be explained by depression alone.…”
mentioning
confidence: 99%